At the center feminism, social science and knowledge - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Advances in gender research ;, 2015)
At the center reflects on how the study of gender has changed and how studying gender has affected our research methods and our knowledge of the world around us. In honor of Bell Hooks' prophetic work, Feminist theory : from margin to center, the volume considers how advances in gender research represent a centering of feminist knowledge and an understanding of the process by which feminist knowledge is constructed. A multinational group of contributors explore relatively new problems such as the integration of transgender study, traditional topics in so far as they incorporate current knowledge and methodological issues pertaining to the effects of research on the researcher and the researched as well as other epistemological matters associated with the construction of gender knowledge. Chapters reflect the strength of a range of qualitative methods including life histories and autoethnography and explore the ways that large sample quantitative analyses can enhance understanding of everyday dilemmas. The interdisciplinary nature of gender studies and the crosspollination of theoretical perspectives are illustrated as is the globalization of gender theory, research and policies.